Characterization of a source of resistance to aflatoxin accumulation in maize - Oluwaseun Ogunola (Wiley, 2021)
Abstract Aflatoxinproduced by the fungus Aspergillus flavus (Link:Fr) can accumulate in maize (Zea mays L.) and poses serious human health and economic concerns, especially in sub‐Saharan Africa. Genetic resistance against A. flavus infection and spread, and subsequent production of aflatoxin, is a key tool for reducing the problem. Some resistant inbred donor lines carry quantitative trait loci (QTL) for resistance that have a sufficiently large phenotypic effect to be used for marker assisted introgression. New sources of resistance, unrelated to previously characterized resistant lines, could carry unique QTL with large phenotypic effect on resistance to complement the previously identified QTL. To this end, CML69, derived from Caribbean Composite germplasm unrelated to previously released resistant lines, was used in QTL mapping to identify and characterize new resistance QTL. Seventeen QTL were identified, although some may be the same genetic region causing QTL identified in more than one environment, indicating that these QTL are stably expressed across environments. These QTL explained 1.8–12.6% each and jointly up to 55% of the phenotypic variation. The largest effect QTL, in particular the QTL in bin 4.08, are most likely the same as has been reported in QTL mapping studies of other resistant maize lines, suggesting both environmental and genetic stability. This stability will be very useful when these QTL are used in maize improvement programs, and single nucleotide polymorphism (SNP) markers linked to these QTL were identified to facilitate this use. CML69, and other lines related to it by pedigree, may make good parents for new aflatoxin resistant hybrids.